Emergence and genomic characterization of hypervirulent ST23/K1 Klebsiella pneumoniae: local epidemiology and global context - Bezdicek, Matej; Jakubickova, Marketa; Bitusikova, Viktoria; Holubova, Ema; Vitkova, Helena; Kocmanova, Iva; Vitkova, Ivana; Zdrazilova Dubska, Lenka; Lengerova, Martina (Frontiers in Microbiology, 2026)
IntroductionHypervirulent Klebsiella pneumoniae (hvKp) of the K1/ST23 lineage is an emerging global threat associated with invasive community-acquired infections. Increasing reports of virulence–resistance convergence highlight the need for genomic surveillance, particularly within Europe where data remain limited. This study characterizes clinical K1/ST23 KP isolates circulating in the Czech Republic and compares them to a global genomic background to evaluate virulence architecture, resistance acquisition and plasmid evolution.MethodsFrom 2017 to 2025, 570 K. pneumoniae isolates from a tertiary-care hospital were screened for hvKp markers. Ninety-six K1/ST23 isolates were subjected to long-read whole-genome sequencing and plasmid reconstruction. Genomes were analyzed alongside 2,463 international ST23 datasets using core-SNV phylogenomics, virulence/resistance profiling, and structural plasmid mapping. Chromosomal integrations were examined through analysis of flanking insertion-sequence contexts.ResultsThe Czech K1/ST23 KP population exhibited high virulence uniformity (95/96 isolates scoring 9/9) without evidence of a single-clone outbreak, instead forming multiple phylogenetic lineages consistent with recurrent introductions. Eighty-three isolates carried pLVPK-like virulence plasmids; however, structural plasticity was prominent. The iro cluster was relocated to conjugative IncFII/rep_cluster_1418 plasmids in two isolates—one carrying additional AMR genes—and was chromosomally integrated via IS1-mediated recombination in three others. Iut was chromosomally integrated via IS903 (IS5 family) with either classical target-site duplication or recombination-associated insertion. Nine virulence–resistance fusion plasmids (IncFIB–IncFII–IncHI1B or IncC-based) were identified, representing early convergence toward MDR-hvKp.ConclusionK1/ST23 KP circulating in the Czech Republic is highly virulent yet genomically diverse, driven by active plasmid exchange, insertion-sequence–mediated chromosomal integration, and emerging virulence–resistance fusion plasmids. Although carbapenemase genes were absent, ESBL determinants and transmissible virulence loci indicate strong evolutionary potential toward MDR-hvKp. Continuous genomic surveillance and early intervention strategies are essential to mitigate future clinical impact.